Hearing Children's Voices: The Role of Public Space in Vulnerable Communities. The case of the Hills of Valparaíso, Chile. Issue 1 (May 2020) - Soto, M; León, J; Escobar, A
Abstract: The relationship of childhood and public space is increasingly distant. Various factors, both social and governmental (from violence to the planning processes themselves), have gradually led to an environment in which what is public becomes alien. In this context, the analysis of public space and its relationship to children's lives must draw attention to not only children's perceptions of these spaces but also the role they should accommodate. In this respect, the research aims to identify children's activity patterns and safety perceptions about public spaces in communities highly vulnerable to socio-natural disasters. To this end, three case studies are presented, corresponding to three public spaces located in the hills of the city of Valparaíso, a territory which, in addition to having a lack of green areas, is characterized by recurring socio-natural disasters such as earthquakes and fires. Additionally, these three public spaces were chosen according to the level of inclusion of the child population in their respective design processes. Six focus groups with children between the ages of 8 and 11 years old who study in educational establishments near the squares were conducted to identify the children's perceptions of these public spaces and understand their roles as safe spaces amid anthropogenic or natural risks. The results show that the children feel more involved in and closer to public spaces when they have participated in their design; however, they do not consider these spaces areas of protection against socio-natural disasters.